Preliminary sizing and study of a hybrid rocket based combined cycle - Hillion, Laurine; Parisse, Jean-Denis; Mangeot, Alexandre (Frontiers in Space Technologies, 2023)
This study investigates the feasibility and performance of a missile propelled by a Hybrid Rocket-Based Combined Cycle (HRBCC) engine, which combines hybrid rocket and air-breathing engines. The HRBCC engine could enable intra and extra-atmospheric hypersonic flight in the future. Using a hybrid rocket engine could bring several advantages as reduced costs, increased reliability and simplicity. This research presents the unique feature of the hybrid rocket engine developed by HyPrSpace and explains its benefits for the conception of a HRBCC system. The performance of the missile was studied in two operational modes: pure rocket and ramjet. The results were then used to develop an in-house code that compared the trajectory of different missiles. Our findings indicate that HRBCC engines provide several advantages over other propulsive technologies and can meet the requirements of various military applications.